The world day of remembrance for road traffic victims - Ramos, M. (22nd Meeting of the United Nations Collaboration for Road Safety, WHO-Unicef, New York, 12-13 April, 2016, 2016)
Brief history of the World Day of Remembrance for Road Traffic Victims, since UN recognition: • UN adoption made this Day known worldwide • Growing number of countries on all continents commemorating the World Day • Number of stakeholders in those countries also growing: - NGOs and road safety professionals, agencies working in crash prevention and the aftermath of road death and injury, institutions and government departments • UN adoption made this Day known worldwide • Growing number of countries on all continents commemorating the World Day • Number of stakeholders in those countries also growing: - NGOs and road safety professionals, agencies working in crash prevention and the aftermath of road death and injury, institutions and government departments